Estimation of the maximum credible hazard in Kuala Lumpur and Singapore due to gigantic Sumatran megathrust earthquakes: based on a comparative study on attenuation laws - Shoushtari, Abdollah Vaez (Springer, 2015)
This paper has classified nine attenuation laws derived for subduction interface earthquakes through a comparative study based on the peak ground accelerations (PGAs) recorded in Peninsular Malaysia and Singapore. The goal of classification was to identify the attenuation laws that were the most compatible with the region. The PGAs predicted by the relations provided by Nabilah and Balendra (Earthq Eng 16:1076–1094, 2012) and Zhao et al. (Bull Seismol Soc Am 96:898–913, 2006) were found to correlate well with the recorded PGAs. The maximum credible hazard in Kuala Lumpur and Singapore was obtained by calculating the acceleration response spectra caused by three great Sumatran megathrust earthquakes (the worst possible earthquake scenarios) using Zhao et al. spectral attenuation law. Current building code in the region requires that buildings should be capable of resisting a notional ultimate lateral design load equals to 1.5 % of the characteristic dead weight, simultaneously applied at each floor (i.e., the minimum design level of buildings equals to ~0.15 m/s2). The results show that the risk level for structures of the two cities with natural period Tn = 1–1.5 s corresponding to 10- and 15-story buildings located on hard soil sites [National Earthquake Hazards Reduction Program (NEHRP) site class C] is high as the demand spectrum due to a worst possible earthquake scenario with moment magnitude (MW) 9.5 and an epicentral distance (Repi) of 600 km from Singapore was noticeably higher than their design level. The results of the present study are applicable in seismic hazard assessment projects in Peninsular Malaysia and Singapore. The most interesting conclusion from the earthquake engineering perspective, however, is that the design spectral shapes specified in IBC 2012 and Eurocode 8 (type 2) codes may not be particularly appropriate for sites that could be affected by large-magnitude, distant earthquakes.